Efeito da idade relativa nas provas de velocidade e saltos do atletismo brasileiro - Barboza Neto, Rui (2022)
Introduction: The Relative Age Effect (RAE) is a concept related to the possible advantage that older athletes would have over younger ones within the same category. However, this phenomenon may or may not arise depending on the modality, sex, age group, level of competitiveness, location, and requirement of the tasks in the modality. For a better understanding of how the RAE behaves in Athletics, in addition to the general analysis of the modality, more detailed analyzes with cuts within the groups of events are necessary. Objective: To analyze the Relative Age Effect on general speed and jumping events in Athletics and segmented between the most and least practiced events. Methods: The 50 best results in the Brazilian Ranking of the CBAt (Confederação Brasileira de Atletismo) of the sprint and jumping events in Athletics of the Under-16 (female and male) and Under-18 (female and male) categories were extracted from the CBAt public website for data analysis. The data were analyzed in their total sample and divided by category. Subsequently, the sample was divided into more practiced events (sprint speed events and horizontal jumps) and less practiced events (hurdles and vertical jumps). Finally, an analysis of the 10 best results in the female category in the horizontal and vertical jump events was carried out. Results: In the sample of the speed event group, in males the effect of relative age was significant for the total sample (χ 2 = 60.26, p<0.001), Sub-16 (χ 2 = 31.29, p<0.001), and Sub -18 (χ 2 = 32.14, p<0.001), while in females there was no significant effect of relative age. In the group of jumping events, there was an effect of relative age for both sexes (Male χ 2 = 40.6, p=0.003 and Fem χ 2 = 9.46, p=0.03), however, when we segregated the sample by age category (U-16 and U-18) the relative age effect was maintained for males (U16 χ 2 = 21.5, p<0.001 and U-18 χ 2 = 19.8, p<0.001), not appearing for females (U-16 χ 2 = 6.18, p=0.1 and U-18 χ 2 = 3.61, p=0.3). By segregating the sample into subgroups in the sprint events, the effect of relative age was found in the total sample of both sexes